The Celebrity Family Endorsement on Instagram Product Advertisement (Case: The Hermansyah) - Sakti Hendra Pramudya (International Journal of Family Business Practices, 2020)
The main purpose of this study is to analyze the consumer’s perception of single celebrity endorsement and celebrity family endorsement in the context of Instagram advertising. Instagram is selected as the research context due to the application has become a new trend in Asia and there are abundant people who use it as a media for promotion. The object of this research is Anang and Ashanty family business. They are a famous celebrity couple in Indonesia which successfully established numerous product lines, as well as a variety of brands and, interestingly, both Anang and Ashanty (along with their children), are the advertisement models of all of their product in the Instagram. The paper comprises of two separate studies. The first study would use 2 x 2 factorial design to compare the Instagram user’s response towards four stimuli of Instagram advertisements. Two stimuli would depict Instagram advertisement of single celebrity endorser (represents by Ashanty) and the other two stimuli would depict Instagram advertisement of celebrity family endorser (represents by Anang and Ashanty family). The stimulus is taken from the original advertisement from the couple’s product lines which represents by one cake product and one acne cream product. The second study is a consumer’s opinion survey which measures respondent’s opinion towards the advertisements. Based on the survey results of 547 Instagram users in Indonesia, it is revealed that celebrity family advertisement emerged higher than single celebrity advertisement for the acne cream product. Hence, it can be concluded that the consumer does value celebrity family endorsement more than individual or single celebrity endorsement. However, further analysis reveals that the engagement only exists in the initial stage (attention) and the middle stage (desire and search) of consumer’s psychological process to purchase a new product due to all of the advertisement is lacking information about the price.Keywords: Family Business Branding, Single Celebrity Endorsement, Celebrity Family Endorsement, Instagram.